Network Analysis of Posttraumatic Stress Disorder Symptoms in a National Sample of U.S. Adults: Implications for the Phenotype and the ICD‐11 Model of PTSD. Issue 1 (26th February 2020) - Cero, Ian; Kilpatrick, Dean G.
Abstract: The phenotype for posttraumatic stress disorder (PTSD) in the fifth edition of the Diagnostic and Statistical Manual of Mental Diseases ( DSM‐5 ) includes 20 symptoms in four clusters. In contrast, the PTSD model in the 11th revision of the International Classification of Diseases ( ICD‐11 ) includes six symptoms in three clusters. Whether those six symptoms are, in fact, the most central symptoms of the PTSD phenotype remains an open question. In a previous network analysis of DSM‐5 PTSD symptoms, Mitchell and colleagues (2017) reported limited overlap between central PTSD symptoms and those in the ICD‐11 model in a national sample of U.S. veterans. The present study sought to replicate and extend upon these findings in a large national sample of U.S. adults ( N = 2, 953). Centrality statistics from both a replication sample (i.e., participants with DSM‐5 PTSD, n = 173) and an extension sample (i.e., participants who had been exposed to potentially traumatic events, n = 2, 468) were moderately strongly convergent with the findings reported by Mitchell et al., r s = .54–.73. Additionally, only three of the six most central symptoms in both the replication and extension samples overlapped with the ICD‐11 model, indicating that the ICD‐11 model (a) failed to include network‐central symptoms of the PTSD phenotype and (b) included extra symptoms that were not network‐central. Several symptoms from the DSM‐5 Criterion D cluster (negative alterations in cognition and mood) that were excluded in ICD‐11 were found to be among the most central PTSD symptoms. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Análisis de redes de síntomas de TEPT en una muestra nacional de adultos de EE. UU.: implicaciones para el fenotipo de TEPT y la CIE‐11 REDES DE SÍNTOMAS DE TEPT El fenotipo para el trastorno de estrés postraumático (TEPT) en la quinta edición del Manual Diagnóstico y Estadístico de Enfermedades Mentales (DSM‐5) incluye 20 síntomas en cuatro grupos. En contraste, el modelo de TEPT en la 11ª revisión de la Clasificación Internacional de Enfermedades (CIE‐11) incluye seis síntomas en tres grupos. Si esos seis síntomas son, de hecho, los síntomas más centrales del fenotipo de TEPT sigue siendo una pregunta abierta. En un análisis de red anterior de los síntomas del TEPT del DSM‐5, Mitchell y colegas (2017) informaron una superposición limitada entre los síntomas del TEPT central y los del modelo ICD‐11 en una muestra nacional de veteranos estadounidenses. El presente estudio buscó replicar y ampliar estos hallazgos en una gran muestra nacional de adultos estadounidenses ( N = 2, 953). Las estadísticas de centralidad de ambas muestras, la de replicación (es decir, participantes con TEPT DSM‐5, n = 173) y la de extensión (es decir, participantes que habían estado expuestos a eventos potencialmente traumáticos, n = 2, 468) fueron moderada a fuertemente convergentes con los hallazgos reportados por Mitchell et al., rs = .54 – .73. Además, solo tres de los seis síntomas más centrales en las muestras de replicación y extensión se superpusieron con el modelo CIE‐11, lo que indica que el modelo CIE‐11 (a) no incluyó los síntomas centrales de la red del fenotipo de TEPT y (b) incluía síntomas adicionales que no eran centrales de red. Se descubrió que varios síntomas del grupo DSM‐5 Criterio D (alteraciones negativas en la cognición y el estado de ánimo) que se excluyeron en CIE‐11 se encuentran entre los síntomas más centrales del TEPT. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Network Analysis of PTSD Symptoms in a National Sample of US Adults: Implications for the PTSD Phenotype and the ICD‐11 Traditional Chinese 標題: 對美國成人樣本的PTSD症狀進行網絡分析:有關PTSD表型與ICD‐11的發現 撮要: 創傷後壓力症(PTSD)在《精神疾病診斷與統計手冊》第五版(DSM‐5)裡的表型, 包含四個聚類20個症狀。相較之下, 《國際疾病分類》第十一版(ICD‐11)的PTSD模型, 則包含三個聚類六個症狀;目前大家仍不清楚那六個症狀是否為PTSD表型最中心的症狀。Mitchell與同僚(2017)先前針對DSM‐5 PTSD症狀的網絡分析指出, 在美國的國家退役軍人樣本中, PTSD中心症狀跟ICD‐11模型的症狀只是有限度地重疊。本研究旨在重複驗證及進一步延伸該發現。樣本為大型的美國成人樣本(N = 2, 953)。重複驗證樣本 (即患有DSM‐5 PTSD的人士, n = 173) 與延伸樣本 (即曾經歷潛在創傷事件的人士, n = 2, 468) 的中心性統計數據, 跟Mitchell et al.的研究發現有中等至強的聚合性 (rs = .54–.73) 。此外, 重複驗證樣本與延伸樣本中, 六個最中心的症狀裡只有三個跟ICD‐11模型重疊, 反映ICD‐11模型(a) 並無包含PTSD表型的網絡中心症狀;(b) 包含了額外、非網絡中心的症狀。ICD‐11中並無包含的數個DSM‐5準則D聚類症狀 (認知與情緒的負面改變), 被發現為最中心的PTSD症狀之一。 Simplified Chinese 标题: 对美国成人样本的PTSD症状进行网络分析:有关PTSD表型与ICD‐11的发现 撮要: 创伤后压力症(PTSD)在《精神疾病诊断与统计手册》第五版(DSM‐5)里的表型, 包含四个聚类20个症状。相较之下, 《国际疾病分类》第十一版(ICD‐11)的PTSD模型, 则包含三个聚类六个症状;目前大家仍不清楚那六个症状是否为PTSD表型最中心的症状。Mitchell与同僚(2017)先前针对DSM‐5 PTSD症状的网络分析指出, 在美国的国家退役军人样本中, PTSD中心症状跟ICD‐11模型的症状只是有限度地重迭。本研究旨在重复验证及进一步延伸该发现。样本为大型的美国成人样本(N = 2, 953)。重复验证样本 (即患有DSM‐5 PTSD的人士, n = 173) 与延伸样本 (即曾经历潜在创伤事件的人士, n = 2, 468) 的中心性统计数据, 跟Mitchell et al.的研究发现有中等至强的聚合性 (rs = .54–.73) 。此外, 重复验证样本与延伸样本中, 六个最中心的症状里只有三个跟ICD‐11模型重迭, 反映ICD‐11模型(a) 并无包含PTSD表型的网络中心症状;(b) 包含了额外、非网络中心的症状。ICD‐11中并无包含的数个DSM‐5准则D聚类症状 (认知与情绪的负面改变), 被发现为最中心的PTSD症状之一。